PENGARUH QUICK RATIO DAN CASH RATIO TERHADAP RETURN ON ASSET PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Gusti Ayu Putu Puspita Dewi; Putu Nuniek Hutnaleontina (UNHI Press, 2021)
Getting..the maximum profit is one of the goals of all companies. Profitability reflects the company's ability to generate profits. A company is said to be healthy if the company can survive in difficult economic conditions, seen from the company's ability to meet financial obligations and carry out stable operations and to maintain its business growth. The research is for now how about effect of liquidity ratios on profitability. Simultaneously, the quick ratio and cash ratio have a positive and significant effect on return on assets. But partially, only the quick ratio has a positive and significant effect on return on assets, as evidenced by the results of t count = 35,076> t table = 1,652 and a significance value of 0,000 < 0,005.